Productive performance of inoculated soybeans and co-inoculada in Cerrado Domínio (Research, Society and Development, 2020)
To increase the efficiency of the biological fixation of nitrogen (FBN) in soybean culture, aiming at elevation of levels of productivity, the use of Co-inoculação is alternative. The combination of symbiotic and diazotrophic bacteria, which produce synergic effect, benefit the plant in greater nodulation and root growth. In this way, the objective in this work was to evaluate qualitative the productive performance of co-inoculação and different ways of applying Bradyrhizobium japonicum and Azospirillum brasilense in soybean culture. The experiment was carried out in the field, at the Experimental Farm on the IF Goiano Campus Ceres in randomized blocks, the treatments being: 1) control; 2) Inoculation with Bradyrhizobium japonicum in the treatment of seeds; 3) Inoculation with Azospirillum brasilense in the treatment of seeds; 4) Co-inoculation of B. japonicum and A. brasilense in the treatment of seeds; 5) Co-inoculation of B. japonicum in the treatment of seeds and A. brasilense at the V3 stage; 6) Co-inoculation of B. japonicum and A. brasilense in the Groove; 7) Co-inoculation of B. japonicum in the treatment of seeds and A. Brasilense in the Groove; 8) Co-inoculation of A. brasilense in the treatment of seeds and B. japonicum in the Groove. The inoculation and Co-inoculação showed no effect on the insertion height of the first pod and mass of a thousand grains. In turn, when the seeds were co-inoculadased via sowing groove There was elevation in the other agronomic characteristics of soybean culture, presenting greater grain productivity.